NATURAL DYE FROM THE BARK OF CASUARINAEQUISETIFOLIA FOR SILK - V. NARAYANASWAMY; K.N. NINGE GOWDA; R. SUDHAKAR (International Journal of Pharma and Bio Sciences, 2013)
The use of natural dyes as an alternative to synthetic dyes has attracted increasing attention in view of hazards and environmental pollution caused by synthetic dyes and pigments. Natural dye was extracted from Casuarina equisetifolia bark, which hitherto was treated as waste material. The dye uptake and fixation as well as the influence of mordants on the colorimetric and fastness properties have been demonstrated. K/S values of the dyed fabrics were also evaluated and the effect of mordant type with different mordanting methods on dyeing was studied. The extracted dye was tested against gram-positive and gram-negative bacteria for antimicrobial activity. The eco-friendliness of the dye was verified by analyzing the metal content, pesticides and amines. The mordant dyed samples showed improved colour values and fastness properties besides exhibiting antibacterial property indicating its potential for use in the textile industry.